2023
DOI: 10.3390/antibiotics12030488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mcr-1 Genes and Characterization of Resistance Mechanisms to Colistin in Escherichia coli Isolates from Colombian Hospitals

Abstract: We report the presence of the mcr-1 gene among 880 Escherichia coli clinical isolates collected in 13 hospitals from 12 Colombian cities between 2016 and 2019. Seven (0.8%) isolates were colistin resistant (MIC ≥ 4 µg/mL). These colistin-resistant isolates were screened for the presence of the mcr-1 gene; five carried the gene. These five isolates were subjected to whole genome sequencing (WGS) to identify additional resistomes and their ST. In addition, antimicrobial susceptibility testing revealed that all E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Other study showed that 83.3% of strains carrying mcr-1 gene showed fosfomycin susceptibility. 62 Beyond UTI as the main focus of fosfomycin prescription, fosfomycin also showed excellent diffusion to various tissues. Thus, it should be considered for managing various other types of infectious caused by MDR, XDR Enterobacterales.…”
Section: Discussionmentioning
confidence: 99%
“…Other study showed that 83.3% of strains carrying mcr-1 gene showed fosfomycin susceptibility. 62 Beyond UTI as the main focus of fosfomycin prescription, fosfomycin also showed excellent diffusion to various tissues. Thus, it should be considered for managing various other types of infectious caused by MDR, XDR Enterobacterales.…”
Section: Discussionmentioning
confidence: 99%